Implementing Comic in Learning English Vocabulary in Pharmacy Students of STIKes Buleleng - Marleni, Kadek Devy; Ridayanti, Putu Windi; Ratnadi, Ni Nyoman Ari (Institut Hindu Dharma Negeri Denpasar, 2020)
The success of the teaching-learning process is not only supported by the students but also by the teacher as central learning. In this case, students and teachers have an equally important role. The students will be enthusiastic in learning when they have good teachers in transfer information, material, and knowledge. Teaching English as a foreign language to adult students is not essay job to do. It needs kinds of strategies in teaching and method to transform knowledge into them. It is because English is difficult and not an essay to be learned for them. English language as a foreign language has so many challenges to be faced when learned it. Many factors showed that English is difficult to be learned by students at a higher level such as they are lack vocabulary, confusing to express their ideas, lazy to practice English, bored in teaching strategy, or media that lecture used. In this situation, the lecture should choose appropriate media, strategy, or method when teaching. And one of the media can be used is comic. Comics are a series of pictures that contain images and balloons to write a story. This research showed that learning by implementing comics was so significant to improve students’ willingness in learning vocabulary. It prof by the increasing mark of students in English objects, the present list was always full and the atmosphere of the classroom is so lively. The class was always happy, enthusiastic, and comfortable to follow the lesson.